Spelling deficits in children with intellectual disabilities: Evidence from a regular orthography - Di Blasi, Francesco Domenico; Vizzi, Francesca; Stimoli, Maria Agatina; Buono, Serafino; Iaia, Marika; Zoccolotti, Pierluigi; Angelelli, Paola (Frontiers in Psychology, 2023)
Introduction In individuals with intellectual disabilities (ID), efficient reading and writing skills promote social integration, self-autonomy, and independence. However, research has mainly focused on reading skills, while evidence on spelling skills is scarce and mostly on English-speaking subjects. In the present research project, we compared the spelling skills of children with intellectual disabilities (ID) learning in Italian, a regular orthography, to those of typically developing children matched for school level. Methods In the first study, the performance on a Passage Dictation Test of forty-four children with ID attending regular classrooms from 4th to 8th grades (mean age = 12.16 years; SD = 1.57) were compared with controls matched for sex and grade. In the second study, a Words and Nonwords Dictation Test was administered (with stimuli varying for lexicality, orthographic complexity, regularity of transcription, and the presence of different types of phonetic-phonological difficulties) to twenty-two children with ID attending regular classrooms from 4th to 8th grades (mean age = 12.2 years; SD = 1.37) and 22 controls matched for sex and grade. In both studies, an error analysis was performed to characterize types of misspellings. Separate ANOVAs were performed on z scores. Results Children with ID generally had a lower performance than controls. In the Passage Dictation Test, they showed a higher number of phonological (and phonetic-phonological) errors than phonologically plausible ones, indicating, as a group, predominant phonological difficulties as compared to lexical-orthographic ones. In the Words and Nonwords Dictation Test, they performed poorly on regular stimuli presenting specific types of phonetic-to-phonological difficulties (geminates, non-continuant consonants) and committed more minimal distance, context-sensitive and simple conversion misspellings. However, deficits in the orthographic-lexical procedure, as indicated by a low performance in words with unpredictable spelling, were present in a high percentage of children. Discussion It is concluded that children with ID have significant spelling difficulties not confined to the orthographic process but also in phoneme-to-grapheme mapping that, in a regular orthography like Italian, should be acquired early and easily.